Transient Receptor Potential Ankyrin 1 Mediates Hypoxic Responses in Mice - Chen, Sichong; Takahashi, Nobuaki; Chen, Changping; Pauli, Jordan L.; Kuroki, Chiharu; Kaminosono, Jun; Kashiwadani, Hideki; Kanmura, Yuichi; Mori, Yasuo; Ou, Shaowu; Hao, Liying; Kuwaki, Tomoyuki (Frontiers in Physiology, 2020)
Transient receptor potential ankyrin 1 (TRPA1) is a non-selective cation channel that is broadly expressed in sensory pathways, such as the trigeminal and vagus nerves. It is capable of detecting various irritants in inspired gasses and is activated during hypoxia. In this study, the role of TRPA1 in hypoxia-induced behavioral, respiratory, and cardiovascular responses was examined through four lines of experiments using TRPA1 knockout (KO) mice and wild type (WT) littermates. First, KO mice showed significantly attenuated avoidance behavior in response to a low (15%) oxygen environment. Second, the wake-up response to a hypoxic ramp (from 21 to 10% O2 in 40 s) was measured using EEG electrodes. WT mice woke up within 30 s when oxygen was at 13–14%, but KO mice did not wake up until oxygen levels reached 10%. Histological analysis confirmed that mild (13% O2) hypoxia resulted in an attenuation of trigeminal neuronal activation in KO mice. Third, the ventilatory response to hypoxia was measured with whole body plethysmography. KO mice showed attenuated responses to mild hypoxia (15% O2) but not severe hypoxia (10% O2). Similar responses were observed in WT mice treated with the TRPA1 blocker, AP-18. These data clearly show that TRPA1 is necessary for multiple mild hypoxia (13–15% O2)-induced physiological responses. We propose that TRPA1 channels in the sensory pathways innervating the airway can detect hypoxic environments and prevent systemic and/or cellular hypoxia from occurring.